2019
DOI: 10.1177/0310057x19839941
|View full text |Cite
|
Sign up to set email alerts
|

Parents welcome follow-up using mobile devices: A survey of acceptability at an Australian tertiary paediatric centre

Abstract: Follow-up for ongoing management and monitoring of patients is important in clinical practice and research. While common, telephone follow-up is resource intensive and, in our experience, yields low success rates. Electronic communication using mobile devices including smartphones and tablets can provide efficient alternatives — including SMS (text), online forms and mobile apps. To assess attitudes towards electronic follow-up, we surveyed 642 parents and carers at Perth Children’s Hospital, targeting demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 7 publications
2
10
0
Order By: Relevance
“…We demonstrated that SMS follow‐up for the collection of longitudinal research data in the postoperative period for a single quantitative variable is feasible in a pediatric population and highly acceptable to parents. This aligns with a previous survey of parents from our institution which found the majority were willing to communicate with the hospital via SMS 8 . The high completion and response rates seen in this study demonstrate that this reported willingness translates well into practice.…”
Section: Discussionsupporting
confidence: 89%
“…We demonstrated that SMS follow‐up for the collection of longitudinal research data in the postoperative period for a single quantitative variable is feasible in a pediatric population and highly acceptable to parents. This aligns with a previous survey of parents from our institution which found the majority were willing to communicate with the hospital via SMS 8 . The high completion and response rates seen in this study demonstrate that this reported willingness translates well into practice.…”
Section: Discussionsupporting
confidence: 89%
“…We note with interest the results of the survey by Smallbone et al., 1 and write to provide additional support for their proposal that electronic follow-up is more efficient than telephone follow-up for clinical purposes.…”
mentioning
confidence: 72%
“…Efficiency and acceptability of an electronic follow-up system (DayCOR) for paediatric patients Nicole LT Tan 1 , Kenneth W Sleeman 2 and John R Sestan 3 We note with interest the results of the survey by Smallbone et al, 1 and write to provide additional support for their proposal that electronic follow-up is more efficient than telephone follow-up for clinical purposes.…”
mentioning
confidence: 97%
“…In comparison, appetite for symptom tracking appears low with one study reporting 49% amongst parents of children with cancer 4 . An Australian study examining mobile phones for follow‐up of paediatric emergency department visits reported acceptability rates of 93% for receiving text messages, 80% for responding to text messages and 69% and 60% for using an app and a website, respectively 8 …”
mentioning
confidence: 99%